宗教の死・自由・幸福― ―岸本英夫における「近代化」について [Death, freedom, and happiness in religion: On Hideo Kishimoto and “modernization”] - Magata, Naoki (Silva Iaponicarum, 2026)
This paper examines the thought of Hideo Kishimoto, a Japanese scholar of religion. Kishimoto’s work has traditionally been divided into two areas: reflections on life, death and mortality, shaped by his experience suffering from cancer; and his post-World War II role as an advisor on Japanese religions to the General Headquarters (GHQ). These two areas have not been considered together, leaving Kishimoto’s thought insufficiently understood as a coherent system. Focusing on the concept of “modernization”, this study therefore provides an integrated account of his scholarship. It shows that he consistently viewed religion as oriented toward human “happiness” and saw modernization as the means to achieve this aim. By unifying two aforementioned areas of research, the study constructs a more accurate understanding of Kishimoto’s thought than has previously existed, inviting reflection on the state of religion in contemporary Japan.